Critical Levels of Copper, Zinc, and Manganese Toxicity in Soil and Tissues of Plants That Cohabit Vineyards in the Pampa Biome - Filipe Nunes de Oliveira; Letícia Morsch; Jean Michel Moura-Bueno; Adriele Tassinari; Edicarla Trentin; Anderson César Ramos Marques; Talita Andreolli; Bianca Goularte Dias; Luciane Almeri Tabaldi; Gustavo Brunetto (Horticulturae)
Old vineyards in production in the Pampa biome have high levels of metals, such as copper (Cu), zinc (Zn), and manganese (Mn). The high metal contents in the soil can damage the growth and development of the cover plant species that cohabit the vineyards. However, it is possible to define the critical toxicity level (CTL) of metals in soil and tissue in order to monitor and define possible strategies for reducing metal inputs and selecting more tolerant species. This study aimed to define the CTL of Cu, Zn, and Mn in the soil and plant tissue of plants present between the rows of vineyards with different cultivation histories in the Pampa biome in South America. For this purpose, soil and plant tissue samples were collected in a native field area (NF), without agricultural cultivation and in two vineyards, vineyard 1 (V1) and vineyard 2 (V2), both with a history of fungicide application. To define the CTL, the foliar concentrations and soil contents of Cu, Zn, and Mn were correlated with the dry mass production of the shoot. The CTLs for Cu, Zn, and Mn in the soil were set at 15, 3.0, and 35 mg kg−1, respectively. In the tissue, CTLs for Cu, Zn, and Mn were estimated at 75, 77, and 380 mg kg−1, respectively. The contents of Cu, Mn, and Zn in the soil of the vineyards are above the CTL. The concentrations of the metals in the tissue varied, with samples above the CTL for Cu and Zn in the vineyards. The values of Cu, Zn, and Mn in NF are below the CTL in soil and tissue. The high contents of Cu, Zn, and Mn in the soil and tissue limited the dry mass production of the plants between the rows of vineyards.